Research on Cumulative Damage Model of Transmission Tower Based on Typhoon Path Prediction Information - Yi TANG; Xiangxiang XU; Bin CHEN; Tao YI (Zhongguo dianli)
Strong typhoons may cause physical damage to the transmission towers in the area where it passes, leading to large-scale blackouts. In order to assist the electric power department to accurately predict the risk of tower collapse and deploy anti-typhoon materials in advance, a cumulative damage model of transmission tower is established based on typhoon path prediction information. Firstly, according to the short-term typhoon forecast information of the meteorological department, the risk tower affected by the typhoon is determined by the method of grid division; Secondly, the basic information of the typhoon from the short-term and short-time dual-time scales and the geographical information of the tower are fully combined to predict the cumulative action time and wind speed of the typhoon. Thirdly, a mathematical model of low-cycle fatigue damage is constructed for towers collapsed due to plastic fatigue under unit time, and the improved Poisson formula is used to obtain the fault probability of towers with different typhoon action times, wind speeds and geographical positions. Finally, the minimum load loss of the power grid is calculated using the DC power flow optimization algorithm. Case study has verified the validity and rationality of the proposed model.